“Silent Wars” Between Migrants’ Children and Teachers, Teachers and Migrant Parents: Gendered “War” - Winniefridah Matsa (Springer, Cham, 2023)
The lives of migrants’ children are characterised by strained relations between them and teachers. Teachers also have negative attitudes towards migrant parents and vice versa. The strained relations are largely caused by lack of teacher–parent partnership, belief and attitudes towards each group. Teachers mock and insult both learners and their parents. The war is suckly and invisible. In fact, there seems to be hatred and belittling of each other, evidenced by attitudes held against each group. Greater effort is made by teachers to conceal the conflicts between teachers and migrants’ children though learners sometimes openly declare war. Migrant parents also attempt to portray positive relations with teachers for the benefit of their children who remain in the hands of these teachers during their absence. There is secret or salient enmity. Caregivers sometimes take advantage of the situation to worsen the wars by reporting to migrant parents what teachers say or do. Although the war is not a gender one, it is more pronounced between male teachers, male learners and male migrants.